The Perceptions on Bilingual-based Materials Approach in English for Educational Technology - Asrifan, Andi; Muthmainnah, .; Mohammed, Mohammed Galal (Modern Perspectives in Language, Literature and Education Vol. 4, 2021)
International travel, mass media, immigration, and the world economy, have made bilingualism mandatory. Baker [1] argues that bilinguals exist in all countries, all social classes, and communities of all ages. Bilingualism may be a challenge to learn English as a Foreign Language (EFL) in Indonesia. The research explored the views of students on the subject of bilingual English teaching materials for education technology. The experience of the students to enhance the future education program. The findings indicate that most students had a strong outlook on using bilingual materials in their English courses and felt that the materials were suitable and easily understood.